(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Technical and Vocational Education (TVE) is geared towards the development of specific skills for economic and social challenges. Considering the high rate of unemployment of TVE Nigerian graduates especially the secondary school leavers and the university graduates, it becomes pertinent to critically examine the role of TVE and proffer strategies for its improvement towards ameliorating the situation. This study therefore ascertains the state of TVE in Nigeria, emerging challenges in TVE and proposed strategies towards enhancing the TVE programme in Nigeria for economic development. The study would be of benefit to the researchers and curriculum planners as it would contribute to literature and enhance the knowledge of the curriculum planners on the strategies to include when planning the curriculum to improve TVE programme in order to reduce the rate of unemployment and poverty in Nigeria.